Science and its social grounding - Krzanowski, Roman (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
Stuart Richie’s book discusses social, political, and cultural influences on science. In a series of well documented cases Richie shows how many of top scientific journals publish poorly executed studies with dubious conclusions. Such publications distort a public image of science as an unbiased search for truth. The roots of such practices, Richie traces to the way science enterprise is done in academia and in private research centers, where only positive and “expected” results are valued. While according to Richie there is a small chance to cure scientific practices from these ills, science itself is and remains the search for truth, even if our social moors make it so much harder.